210 Recurrence after radical hysterectomy in early cervical cancer patients. (18th September 2019) - Sousa, M; Cintra, G; Vieira, M; Reis, R; Santos, M; Andrade, CE
Abstract : Objectives: The objective of this study is to estimate the recurrence rate in women with early-stage cervical cancer (stages IA1 with LVSI, IA2 and IB1) underwent radical hysterectomy and pelvic lymphadenectomy and evaluate the recurrence by the surgical approach (laparoscopy - conventional or robotic vs laparotomy). Methods: A retrospective study was conducted in patients who underwent radical hysterectomy and pelvic lymphadenectomy for early stage cervical cancer at Barretos Cancer Hospital from January 2009 to March 2017. Were evaluate the recurrence rate, surgical approach and the pathologic risk factors for recurrence The statistical analyses were performed using Chi-square and Fisher tests. Results: An evaluation was conducted of 139 patients. The rate of tumor recurrence was 10.8% (15). The surgical approach was laparoscopy (conventional or robotic) in 107 (77%) patients and laparotomy in 32 (23%) patients. About the patients with recurrence, 13 patients underwent a laparoscopy approach, and 2 patients underwent a laparotomy approach. Conclusions: In conclusion, it can be suggested that patients underwent radical hysterectomy with pelvic lymphadenectomy by laparoscopic approach have more risk of recurrence that laparotomy approach, according to the results of LAAC trial. This study has some limitations like to be a retrospective study. However, it has satisfactory number of patients included, performed in a single center, where the conduct in the cases of early stage cervical cancer and the surgical technique of radical hysterectomy are standardized and do not suffer major changes among surgeons.